Minimally Invasive Approaches in Pediatric Urolithiasis. The Experience of Two Italian Centers of Pediatric Surgery - Destro, Francesca; Selvaggio, Giorgio Giuseppe Orlando; Lima, Mario; Riccipetitoni, Giovanna; Klersy, Catherine; Di Salvo, Neil; Marinoni, Federica; Calcaterra, Valeria; Pelizzo, Gloria (Frontiers in Pediatrics, 2020)
Background Over the last 30 years, the incidence of pediatric urolithiasis (PU) has been increasing and the surgical management has evolved towards a minimally invasive approach (MIA). We reported the experience of two Centers of Pediatric Surgery in the management of PU, focusing on MIA as first choice in treatment. Methods Data were retrospectively analyzed from October 2009 to October 2019 in children with urolithiasis who were admitted to two referral Italian Centers of Pediatric Surgery. Demographic and clinical data of the patients, features of the urolithiasis, type of surgery were considered. Results Seventy patients (7.3±5.0 years) with normal renal function were treated for calculi in the pyelocaliceal system (45.7%), ureter (34.3%), bladder (4.3%), urethra (1.4%) and multiple locations (14.3%). Size of calculi was>10 mm in 55.7% of cases (kidney>bladder/urethra>multiple>ureter, p=0.01). Symptoms were present in 75.7% of patients. Family history was positive in 16.9% of cases. MIA was performed in 59 patients (84.3%): 11.8% shockwave lithotripsy (kidney>ureter>multiple); 32.2% ureteral retrograde surgery (ureteral>other localizations); 30.5% retrograde intrarenal surgery (kidney>other localizations) and 25.4% other procedures including percutaneous nephrolithotomy, cystoscopic bladder stone removal or laser cystolithotripsy (kidney>bladder>multiple). Preoperative stenting was necessary in 52.8% of cases. Four MIA procedures (6.9%, kidney>ureter/multiple) were converted to open surgery. Open surgery was required as first approach in 15.7% of patients (kidney>ureter>multiple) who needed urgent surgery or had associated congenital renal anomalies. In 18/70 of children (25.7%), with prevalence of stones in kidney and multiple location (p<0.01), a second procedure completed the treatment (88.8% MIA). Intraoperative difficulties were recorded in 8.5% of cases, without difference between location and size of calculi. Late complications (5.7%) were related to displacement and infection of the ureteral stent. Conclusions MIA resulted to be feasible in more than 75% of primary surgery and in more than 85% of cases requiring a second procedure. Preoperative stent was mandatory in more than 50% of children. The technological evolution allowed to overcome many of the technical difficulties related to the approach to the papilla and lower calyxes. Open surgery is reserved for selected cases and endoscopic surgery represents the best choice of treatment for PU.